Influence of rumen fluid inoculation on incidence of sickness in newly arrived feeder calves - K.K. Bolsen; S. Armbruster; Homer K. Caley -1922; G. Fink; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1974)
Inoculating newly arrived feeder calves with 250 ml. rumen fluid did not stimulate weight gain or decrease sickness. One hundred seventy steer calves were used in the 31 day study.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Rumen; Calves; Sickness; Weight gain